Developing academic literacies: A faculty approach to teaching first-year students - Dooey, Patricia Mary; Grellier, Jane (Journal of Academic Language and Learning, 2020)
With increasing diversity among students seeking higher education places in the past two decades, Australian universities are under constant pressure to juggle the competing demands of maintaining student enrolments, achieving rankings, and building a strong reputation in a competitive market, while ensuring the academic literacies of all students. As a result of increasing financial constraints, many universities have been forced to make economies of scale by creating large first-year units that aim to develop the literacies of students across many and varied programs within the same unit of study. This paper reports on one faculty’s attempt to support first-year student success within the constraints of such an environment. The investigation focused on the two-fold initiative of embedding academic language and learning practices within a large, multi-disciplinary unit, and complementing it with an academic writing intervention for students identified as likely to benefit from this. A diverse range of students undertook this dual program, including some for whom English was an additional language (EAL), some mature aged students, and some who were first in their families to undertake university studies. A mixed-methods approach was used to determine any improvements in the performance of these participating students. These students were found to have built a strong foundation for the rest of their studies, and specialist faculty academics believed that the dual program prepared students well for their future disciplinary studies. The benefits of adopting such a collaborative approach are worthy of consideration by educational leaders striving to support student success in the face of the multi-faceted challenges of today’s higher education arena.